Uslub Tasybih dalam Novel Arsis Karya Ahmed Al-Hamdan: Analisis dan Tujuannya - Aryanto, Redi; Rohanda, Rohanda; Komarudin, Edi (STIQ Amuntai, 2025)
This research contains an analysis of tasybih in the novel Arsis by Ahmed Al-hamdan. In this novel, there is a language style with meanings and various redactions that are still vague if not understood with the science of bayan. The purpose of this research is to determine the types and objectives of tasybih based on the bayan science approach. Qualitative description is the method used in this study. This research includes library research-based research that uses the novel Arsis by Ahmed Al-Hamdan as a data source. And sentences that contain tasybih in the novel as a type of data. Data provision using the technique of watching and recording. The data will be studied, then marked and recorded, and then analyzed with the analysis of the science of bayan. The result of this research is that the novel Arsis by Ahmed Al-Hamdan has tasybih mursal, tasybih mufashshal, tasybih mujmal, and tasybih baligh. Meanwhile, tasybih mu'akkad is not found in the novel. The purpose of tasyb³h contained in the novel only includes taqriru halil musyabbah, baynu halil musyabbah, baynu imknil musyabbah, baynu miqdri hlil musyabbah, and taqb³hul musyabbah. While tazyinul musyabbah is not found in the novel. This research strengthens the theory and description of the understanding of tasyb³h based on the analysis of the novel Arsis by Ahmed Al-Hamdan.